PERJANJIAN PERKAWINAN PASCA PERKAWINAN: KAJIAN UNTUK MENCIPTAKAN PARAMETER YURISPRUDENSI (STUDI KASUS PENETAPAN PENGADILAN AGAMA BANTUL NOMOR 0211/PDT.P/2013/PA.BTL) - Usemahu, Rezki Fitriah; Soleh, Mohammad Faisol; Wahid, Abdul; Eka Saputri, Riski Marita (Jurnal Yuridis, 2016)
Jurisprudence as a source of law in Indonesia is perceived as a form of justicewithin the legal system for its social orientation. However, problem arises when itrules out the written positive norms in the existing laws. On the other hand, thelegal status of jurisprudence in Indonesia, that is governed under the principle ofthe persuasive force of precedent, affirms that judges are not bound to previousjurisprudence, this results in the freedom of ratio decidenci in deciding caseseither those which are based on jurisprudence or not. The need of restricting thisfreedom becomes urgency in formulating the ideal parameters of properjurisprudence to be a consideration in case decision, as well as the philosophical,juridical, historical, and sociological background which are ideal elements inmeasuring jurisprudences, are to be taken into account in case decision.